2020
DOI: 10.3390/pathogens9110958
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Markers Associated with Fecal Shedding of the Feline Enteric Coronavirus (FECV)

Abstract: The Feline coronavirus (FCoV) can cause a fatal disease, the Feline Infectious Peritonitis. Persistent shedders represent the most important source of infection. The role of the host in FCoV fecal shedding is unknown. The objective of this study was to develop gene markers and to test their associations with FCoV shedding patterns. Fecal samples were taken from 57 cats of 12 breeds on the day 0 and after 2, 4 and 12 months. Variation from persistent and/or high-intensity shedding to no shedding was observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Comparisons including all candidate genes and comparisons made for genes associated with fecal shedding at p uncorrected < 0.01 and at p > 0.05 in our previous study [ 19 ] revealed specific clustering patterns of genes associated at p corrected < 0.01.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Comparisons including all candidate genes and comparisons made for genes associated with fecal shedding at p uncorrected < 0.01 and at p > 0.05 in our previous study [ 19 ] revealed specific clustering patterns of genes associated at p corrected < 0.01.…”
Section: Resultsmentioning
confidence: 88%
“…Population parameters of nine haplotypes ( NCR1-D , NCR2-M/A , NCR2-S , SLX4IP-A , SNX5-A , SNX5-B , SNX5-C , SNX5-D , SNX5-E ) associated with FCoV shedding in our previous study [ 19 ] are summarized in Supplementary Material SM4 . Data for all haplotypes analyzed are in Supplementary Table ST3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations